Gut Microbiota, Short-Chain Fatty Acids, and Herbal Medicines - Feng, Wuwen; Ao, Hui; Peng, Cheng (Frontiers in Pharmacology, 2018)
As an important source for traditional medical systems such as Ayurvedic medicine and traditional Chinese medicine, herbal medicines have received a lot of attention all over the world, especially in developing countries. Over the past decade, studies on gut microbiota have generated rich information for understanding how gut microbiota shape the functioning of our body system. In view of the importance of gut microbiota, the researchers engaged in studying herbal medicines have paid more and more attention to gut microbiota and gut microbiota metabolites. Of a variety of gut microbiota metabolites, short-chain fatty acids (SCFAs) have received most attention because of their important role in maintaining the hemostasis of hosts and recovery of diseases. Herbal medicines, as an important resource provider for production of SCFAs, have been demonstrated to be able to modulate gut microbiota composition and regulate SCFAs production. In this mini-review, we summarize current knowledge about SCFAs origination, the role of SCFAs in health and disease, the influence of herbal medicine on SCFAs production and the corresponding mechanisms. At the end of this review, the strategies and suggestions for further research of SCFAs and herbal medicines are also discussed.